Role of Translanguaging in Second Language Education - Paudel, Khimananda (English Language Teaching Perspectives, 2024)
Translanguaging, using multiple languages in a language classroom with the intension of achieving certain goals of enabling learners to understand the content is not a novel thing through out the historical records of language teaching. The grammar-translation method propagated the use of more than one language in teaching for the first time. Translanguaging, enables a teacher to reduce the monotony in the classroom since it allows him/her to use more than one language and the language is chosen preferably. The language will be used for exchanging the connotation regarding the content taught in a language classroom. This paper investigates the function of translanguaging within a second or foreign language context in general, particularly in Nepal. The study has been conducted qualitatively since it incorporated themes based on the chosen topic, the theme is supported by the argumentation and the argumentation has been made from the citation of previous studies. Therefore, the data for the present study is from secondary sources which comprise published articles, journals, and other academic works that have been published in the leading publishing houses in the world. The study concludes that using translanguaging enabled the ESL/EFL teachers to teach effectively and they do not need to depend on the target language whenever a difficult situation arose. Similarly, it impeded the smooth learning proficiency in the desired language in the sense that there was domination and over-dependency on the mother tongue, which only enabled the learners to learn content through their mother tongue. The study suggests that judicious use of translanguaging should be made for effective teaching and learning.